Islamic Philosophy of Scientific Explorations and Modern Science: Analytical Study from Social Policy Perspective - Ambreen Kamil; Sadaf Abbasi; Dr. Muhammad Umer Hayat; Gulzameen Kamil; Dr. Naseem Mahmood; Dr. Hafiz Muhammad Idrees (Al-Qanṭara, 2023)
This research article thoroughly examines Islamic philosophy about scientific exploration and its accordance with contemporary scientific principles. This study seeks to explore the historical evolution of Islamic philosophy, its fundamental principles, and its impact on diverse scientific fields, to illuminate the significant impact of Islamic thought on contemporary scientific advancements. The article commences with an introductory section that emphasizes the importance of comprehending the Islamic viewpoint on science within the framework of contemporary scientific progress. The subsequent section of this paper examines the historical progression of Islamic philosophy, commencing with the early Islamic era and the translation endeavor of Greek texts, and subsequently delving into the noteworthy contributions made by influential Islamic philosophers, namely Al-Kindi, Al-Farabi, Ibn Sina, and Ibn Rushd. These philosophers were instrumental in the assimilation of Greek and Mediterranean knowledge into Islamic thought, facilitating a symbiotic connection between rationality, religious belief, and scientific investigation. This paper examines the fundamental principles of the Islamic philosophy of science, encompassing the notions of Tawhid, fitrah, and the pursuit of knowledge. These concepts delve into the unity and oneness of God, the inherent inclination towards knowledge, and the active seeking of knowledge, respectively. These principles underscore the harmonious coexistence of faith and reason, promoting a comprehensive approach to scientific inquiry. This article undertakes an analysis of the congruence between Islamic philosophy and contemporary scientific principles, emphasizing commonalities such as the quest for veracity, concrete evidence, and rationality. The text also explores the impact of Islamic philosophy on diverse scientific domains, such as math, astronomy, healthcare, optics, and chemistry, highlighting the progress achieved by Islamic philosophers in these areas. This paper explores contemporary viewpoints regarding the Islamic philosophy of science, focusing on the analysis of scholarly contributions by modern Islamic intellectuals who have engaged with the intersection of Islam and science. The article wraps up by recognizing the difficulties and promising directions for future research, stressing the importance of interdisciplinary study and teaching. This research article offers a thorough examination of the Islamic philosophy surrounding scientific exploration, emphasizing its historical importance and continued relevance in shaping contemporary scientific advancements.